The Effect of Incentives, Motivation, and Leadership on Sales through Employee Performance - Aldian, M. Nabil Daffany; Safirin, Moch. Tutuk (Borong Newinera Publisher, 2025)
This research investigates the effects of incentives, motivation, and leadership on sales improvement, considering employee performance as a mediating variable, within the context of CV. Sendy Leather. A quantitative research design was applied, employing the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through SmartPLS 4 software. The study involved 44 participants from both the production and marketing departments. Findings reveal that incentives and leadership significantly impact employee performance, whereas motivation does not. Moreover, only performance demonstrates a significant direct effect on the improvement of sales. The direct influence of incentives, motivation, and leadership on sales was found to be statistically insignificant. Additionally, the mediation analysis indicates that employee performance does not significantly mediate the relationship between the independent variables and sales improvement. The values obtained from R-square, Q-square, F-square, and path coefficient assessments highlight that employee performance plays a central role in enhancing sales outcomes.